Genome-Wide CRISPR Screen Identifies RACK1 as a Critical Host Factor for Flavivirus Replication - Shue, Byron; Chiramel, Abhilash I.; Cerikan, Berati; To, Thu-Hien; Frölich, Sonja; Pederson, Stephen M.; Kirby, Emily N.; Eyre, Nicholas S.; Bartenschlager, Ralf F. W.; Best, Sonja M.; Beard, Michael R. (Journal of virology, 2021)
Cellular factors are critical in all facets of viral lifecycles, where overlapping interactions between the virus and host can be exploited as possible avenues for the development of antiviral therapeutics. Using a genome-wide CRISPR knockout screening approach to identify novel cellular factors important for flavivirus replication we identified RACK1 as a pro-viral host factor for both mosquito- and tick-borne flaviviruses in addition to SARS-CoV-2. Cellular factors have important roles in all facets of the flavivirus replication cycle. Deciphering viral-host protein interactions is essential for understanding the flavivirus life cycle as well as development of effective antiviral strategies. To uncover novel host factors that are co-opted by multiple flaviviruses, a CRISPR/Cas9 genome wide knockout (KO) screen was employed to identify genes required for replication of Zika virus (ZIKV). Receptor for Activated Protein C Kinase 1 (RACK1) was identified as a novel host factor required for ZIKV replication, which was confirmed via complementary experiments. Depletion of RACK1 via siRNA demonstrated that RACK1 is important for replication of a wide range of mosquito- and tick-borne flaviviruses, including West Nile Virus (WNV), Dengue Virus (DENV), Powassan Virus (POWV) and Langat Virus (LGTV) as well as the coronavirus SARS-CoV-2, but not for YFV, EBOV, VSV or HSV. Notably, flavivirus replication was only abrogated when RACK1 expression was dampened prior to infection. Utilising a non-replicative flavivirus model, we show altered morphology of viral replication factories and reduced formation of vesicle packets (VPs) in cells lacking RACK1 expression. In addition, RACK1 interacted with NS1 protein from multiple flaviviruses; a key protein for replication complex formation. Overall, these findings reveal RACK1’s crucial role to the biogenesis of pan-flavivirus replication organelles. IMPORTANCE Cellular factors are critical in all facets of viral lifecycles, where overlapping interactions between the virus and host can be exploited as possible avenues for the development of antiviral therapeutics. Using a genome-wide CRISPR knockout screening approach to identify novel cellular factors important for flavivirus replication we identified RACK1 as a pro-viral host factor for both mosquito- and tick-borne flaviviruses in addition to SARS-CoV-2. Using an innovative flavivirus protein expression system, we demonstrate for the first time the impact of the loss of RACK1 on the formation of viral replication factories known as 'vesicle packets' (VPs). In addition, we show that RACK1 can interact with numerous flavivirus NS1 proteins as a potential mechanism by which VP formation can be induced by the former.